Activity of cefoperazone and two beta-lactamase inhibitors, sulbactam and clavulanic acid, against Bacteroides spp. correlated with beta-lactamase production. - Crosby, M A (1982)
A total of 102 isolates of Bacteroides spp. were studied for beta-lactamase production and susceptibility to cefoperazone alone or in combination with either of the beta-lactamase inhibitors sulbactam and clavulanic acid. The geometric mean minimal inhibitory concentration of cefoperazone alone was 31.5 micrograms/ml and when combined with 10 micrograms of sulbactam per ml or 2 micrograms of clavulanic acid per ml was reduced to 5.4 and 9.2 micrograms/ml, respectively. When bacterial suspensions were tested for beta-lactamase production with nitrocefin, 91 (89.2%) of these isolates produced the enzyme. The geometric mean minimal inhibitory concentrations of cefoperazone rose only slightly for isolates with low or intermediate enzyme activity but rose significantly for those with high activity. The addition of EDTA to cefoperazone significantly more frequently enhanced the activity of cefoperazone against beta-lactamase-negative as opposed to beta-lactamase-positive isolates. Furthermore, EDTA resulted in synergistic activity of the cefoperazone-sulbactam combination on beta-lactamase-positive isolates for which the combination had previously not shown a synergistic effect. This study demonstrates the relationship between beta-lactamase production and the resistance of Bacteroides spp. to cefoperazone and shows that inhibition of these enzymes can reverse this resistance.